Colloidal Synthesis of Cu2SxSe1–x Hexagonal Nanoplates and Their Transformation to CdSxSe1–x and ZnSxSe1–x by the Cation‐Exchange Reaction. (25th July 2013) - Han, Shi‐Kui; Gong, Ming; Wang, Ze‐Ming; Gu, Chao; Yu, Shu‐Hong
<x xml:space="preserve">Abstract</x> Hexagonal Cu2S1‐xSex nanoplates (x ≠ 1) can be directly synthesized by a colloidal solution reaction using CuCl, S, and SeO2 as precursors, which can be further transformed into well‐crystallized wurtzite CdSxSe1‐x and ZnSxSe1‐x hexagonal nanoplates and zincblende CdSe and ZnSe tetrahedral nanocrystals, respectively, by the cation‐exchange reaction. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>